'A material influence imperceptibly exercised on the taste and judgement of the public': The Burlington Fine Arts Club and the history of collecting. Review of: Stacey J. Pierson, Private Collecting, Exhibitions, and the Shaping of Art History in London. The Burlington Fine Arts Club. Issue 20 (June 2019) - Donnelly, Eloise
No abstract available